Exploring Open Educational Resources for College Algebra - Chiorescu, Marcela (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
It is estimated that the average student spends around 1200 USD on books and supplies every school year; thus, textbook affordability has become more and more of a challenge for students. Replacing traditionally expensive learning resources with open educational resources (OER) can have a great impact in the reduction of cost for post-secondary education and student learning. With these benefits as a backdrop, this article describes a case study in which one college instructor adopted OER for College Algebra, offered as a hybrid learning model. This paper discusses this experience with adopting such materials and their impact on student success.